Sustainable development in Latin America and the Caribbean : follow-up to the United Nations development agenda beyond 2015 and to Rio+20 (UN New YorkUS, 2013)
Provides a brief account of the region's progress towards achievement of the Millennium Development Goals, focusing on the gaps and estimating the resources needed to close them. Reviews some of the public policy success stories in achieving Goal 1. Sets out some guidelines for moving towards more inclusive and integrated social protection systems. Examines the potential direction of a post-2015 development agenda, weighing the region's current situation, the new challenges it faces , and the need to move towards a sustainable development model.
Keywords: SUSTAINABLE DEVELOPMENT